Acute and chronic magnetic resonance imaging of human herpesvirus-6 associated encephalitis - Crawford, John R.; Chang, Taeun; Lavenstein, Bennett L.; Mariani, Brian (Journal of Pediatric Neurology, 2009)
Human herpesvirus-6 (HHV-6) has been associated with central nervous system encephalitis in immunocompetent children. To determine acute and chronic changes on magnetic resonance imaging (MRI) of a series of consecutive pediatric immunocompetent patients diagnosed with HHV-6 associated encephalitis. A retrospective review of acute and chronic MRI findings of immunocompetent children diagnosed with HHV-6 associated encephalitis from 2001–2008 was performed. Diagnosis was established by real time polymerase chain reaction using HHV-6 U77 helicase gene-specific primers on cerebrospinal fluid during the acute phase of illness, excluding other known causes of encephalitis. Seven patients (four girls, ages 9 months–7 years) were diagnosed with HHV-6 associated encephalitis from 2001–2008. MRI abnormalities were present in six of seven patients. Three had bithalamic signal abnormalities on T2 weighted sequences that mimicked metabolic or demyelinating disease. All patients with MRI abnormalities had diffuse signal changes in the brainstem (n = 5) and/or cerebellum (n = 4). One patient with diffuse abnormalities in cortical grey and white matter, hippocampus, and cerebellum showed complete resolution of MRI findings after 1 month. Five patients had extensive necrosis of the acutely affected regions on follow up MRI 3 to 16 months post diagnosis. HHV-6 associated encephalitis can occur in immunocompetent children with a myriad of acute and chronic necrotizing changes on MRI. MRI abnormalities were seen predominantly in the thalami, brainstem, and cerebellum; and may be reflective of anatomical viral tropism. HHV-6 should be considered in the differential diagnosis of unexplained MRI changes in patients with encephalitis.
Keywords: Human herpesvirus-6; encephalitis; child; HHV-6